Cost-Benefit Analysis of Preventive Programs in the National Health System - Syaiful Bachri; Restidar Soedarto; Azmi Wijayati (International Journal of Health Sciences, 2026)
Abstract Preventive programs within the national health system play a crucial role in improving public health while simultaneously reducing long-term healthcare costs. This study aims to analyze the economic benefits versus costs of implementing preventive programs. The method used is a cost-benefit analysis approach , incorporating literature studies and secondary data from various national and international health sources. The results indicate that investments in preventive programs such as immunization, early screening, and health education provide significant economic benefits, including reduced disease burden, increased productivity, and improved health system efficiency. Therefore, preventive programs deserve to be a priority in national health policy. Keywords: Cost-Benefit Analysis , Preventive Program, National Health System, Health Efficiency